Impact of Pyrolysis Temperature and Jatropha Seed Adhesive on the Properties of Bio-charcoal from Young Coconut Waste - Khairul Anwar; Mahidin Mahidin; Ichwana Ramli; Muhammad Faisal; Agustami Sitorus (The University of Lampung, 2024)
This study assesses the characteristics of bio-charcoal from young coconut waste with the effect of variations in pyrolysis temperature and the addition of Jatropha seed adhesive. The physical and chemical parameters of bio- charcoal from three temperature variation treatments (380°C, 430°C, and 480°C) and three adhesive concentrations (15%, 20%, and 25%) were analyzed, including moisture content, ash content, volatile matter, calorific value and fixed carbon. In addition, the application of ANOVA and DMRT were used to evaluate the significant differences between the various treatments with significant p-value ≤ 5%. The optimal result was obtained at temperature of 430°C and 25% adhesive indicating a calorific value of 6421 cal/g, moisture content of 6.1%, ash content of 7.6% volatile matter of 7.7% and fixed carbon of 78.7%. The findings reveal that adhesive content significantly affects bio-charcoal quality, while temperature variations influence moisture content and heating value. This study concludes that optimizing temperature and adhesive concentrations can yield high-quality bio-charcoal, offering a cleaner, sustainable source. Keywords: Adhesive, DMRT, Jatropha curcas, Pyrolysis, Young coconut waste.